Cladding material and method for manufacturing cladding material

By controlling the undulation of the copper layer and selecting the appropriate aluminum alloy material, the problem of exposed aluminum layer in the cladding material is solved, achieving efficient lightweighting and stability improvement.

CN119730971APending Publication Date: 2025-03-28PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380054629.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-02
Filing Date
2023-07-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When manufacturing cladding materials with three-layer structures, excessive fluctuations of the copper layer cause the aluminum layer to be exposed, causing corrosion problems, and at the same time, the resistance of pure copper materials is increased, affecting electrical characteristics.

Method used

By controlling the manufacturing conditions of the cladding material, ensuring that the undulation of the copper layer is within a reasonable range, the preferred aluminum alloy material is used to reduce the surface exposure of the aluminum layer, and a stable layer structure is formed through specific rolling steps and heat treatment methods.

Benefits of technology

It achieves a lightweight effect of more than 50% without increasing resistance, and effectively suppresses the surface exposure of the aluminum layer, improving the stability and service life of the cladding material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730971A_ABST
    Figure CN119730971A_ABST
Patent Text Reader

Abstract

Provided are: a cladding material which can be reduced in weight by 50% or more than that of a pure copper material (C1020) while suppressing the resistance to be low, and which is desirably suitable for a conductor for alternating current; and a method for producing the cladding material. The cladding material is formed by sequentially laminating and crimping a first copper layer, an aluminum layer and a second copper layer; when the average total thickness is TP, the average layer thickness of the aluminum layer is TA, the average layer thickness of the first copper layer is TC1, the maximum layer thickness TC1MAX and the minimum layer thickness TC1MIN of the first copper layer in the measurement object range of the average layer thickness TC1 are TC1, the average layer thickness TC2 of the second copper layer is TC2, and the maximum layer thickness TC2MAX and the minimum layer thickness TC2MIN of the second copper layer in the measurement object range of the average layer thickness TC2 are TP and TA, TB and TA respectively. 0.5 mm < = TP < = 2.0 mm, 6 < = TA / TC1 < = 26, 6 < = TA / TC2 < = 26, 1.0 < = TC1MAX / TC1MIN < = 3.0, and 1.0 < = TC2MAX / TC2MIN < = 3.0 are satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cladding material and a method for producing the cladding material, for example, to a cladding material suitable for a conductor for alternating current and a method for producing the cladding material. Background Art

[0002] For example, in electrical or electronic equipment (hereinafter referred to as current devices) such as vehicle-mounted devices, portable communication devices, portable chargers or wireless power supplies, most of them use pure copper materials such as C1020 or C1100 of the Japanese Industrial Standards (JIS) specifications with low resistance and excellent conductivity, regardless of direct current or alternating current. For such current devices, it is strongly required to be lightweight in order to reduce the load when moving or carrying. Therefore, it is considered to use aluminum materials such as A1050 or A1100 of the JIS specifications, which have a specific gravity of about 2.7 and are about 70% lighter than pure copper, instead of using pure copper materials with a specific gravity of 8.94 and heavy. Aluminum materials are very cheap compared to pure copper materials. If they can be used, it will also help reduce the cost of current devices. The specific gravity of aluminum materials is smaller than that of pure copper materials, which is conducive to the lightweight of current devices, but the resistance is larger than that of pure copper materials, and there is a possibility that the electrical characteristics required by the current device cannot be obtained. Regarding the resistance, if it is expressed as conductivity, for example, C1020 is about 100% of the International Annealed Copper Standard (IACS), while A1050 is about 60% IACS.

[0003] Therefore, it is considered effective to use a clad material composed of pure copper material and aluminum material by replacing part of the pure copper material with aluminum material instead of replacing all of the pure copper material with aluminum material. For example, a clad material with a three-layer structure (copper layer-aluminum layer-copper layer) is disclosed in Patent Document 1. In the clad material, the overall thickness is 0.25mm to 4mm, the thickness of the copper layer is 0.01mm to 0.8mm, and the thickness of the aluminum layer is 0.2mm to 2mm. The clad material has an alloy layer with a thickness of 0.01mm to 0.4mm between the copper layer and the aluminum layer. The clad material is manufactured by warm rolling (clad rolling) in which the copper plate, the aluminum plate and the copper plate are pressed together in this order, taking into account the difference in deformation resistance. The deformation resistance of the aluminum plate has been disclosed in Non-Patent Document 1, for example.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-143257

[0007] Non-patent literature

[0008] Non-patent document 1: Deformation resistance of various aluminum alloys, author (Nakanishi Kenji, Kamiya Shunpei, Nakahara Koki, Shimizu Yoshitomo, Matsuda Gohiko), Kagoshima University repository contents (http: / / hdl.handle.net / 10232 / 510), Kagoshima University Faculty of Engineering Research Report (1999, No. 41, pp. 1-5) Summary of the invention

[0009] Problems to be solved by the invention

[0010] In the cladding material of the three-layer structure (copper layer-aluminum layer-copper layer), in order to achieve further weight reduction without changing the overall thickness, it is considered to relatively reduce the thickness of the copper layer by further increasing X, which is the thickness ratio of the aluminum layer when the thickness ratio of the three layers (copper layer: aluminum layer: copper layer) is expressed as 1:X:1. For example, in order to replace the pure copper material containing C1020 with a cladding material composed of a copper layer containing C1020, an aluminum layer containing A1050, and a copper layer containing C1020 to achieve a weight reduction of 50% or more, it is sufficient to constitute a cladding material that satisfies X≧5.

[0011] However, when a cladding material having a three-layer structure (copper layer-aluminum layer-copper layer) satisfying X≧5 is manufactured by rolling, thickness variations (fluctuations) may occur in the copper layer. In the case of excessive fluctuations in the copper layer, the aluminum layer may separate from the copper layer, and a portion of the aluminum layer may sometimes be exposed to the surface of the cladding material. When the aluminum layer is exposed to the surface of the cladding material, the exposed portion of the aluminum layer is susceptible to corrosion due to the natural potential difference between the aluminum layer exposed to the surface and the copper layer surrounding it. In view of the problem of surface exposure of the aluminum layer, it is considered to further increase the thickness of the copper layer, but the lightweight effect obtained by replacing the pure copper material with the cladding material becomes smaller, so it is not satisfactory.

[0012] The object of the present invention is to provide a cladding material with a three-layer structure (copper layer-aluminum layer-copper layer) and a method for manufacturing the cladding material, which can suppress the resistance to a small level while achieving a weight reduction of more than 50% (preferably more than 55%) compared with pure copper material (C1020), and ideally to provide a cladding material suitable for a conductor for alternating current and a method for manufacturing the cladding material.

[0013] Technical means of solving problems

[0014] The inventors have conducted a detailed investigation and study on the relationship between the thickness variation (undulation) of the copper layer constituting the cladding material and the surface exposure of the aluminum layer, and have successfully identified the upper limit of the undulation of the copper layer that is unlikely to cause the surface exposure of the aluminum layer. Furthermore, through subsequent efforts and designs, the manufacturing conditions of the cladding material that can suppress the generation of excessive undulation of the copper layer have been discovered, thereby achieving the present invention.

[0015] That is, the cladding material of the present invention is a cladding material composed of a first copper layer, an aluminum layer, and a second copper layer stacked and pressed in this order, and when the average total thickness of the cladding material is T P The average thickness of the aluminum layer is T A , the average thickness of the first copper layer is T C1 , the average layer thickness T C1 The maximum thickness of the first copper layer within the measurement object range is T C1MAX and the minimum layer thickness is T C1MIN , the average thickness of the second copper layer is T C2 , the average layer thickness T C2 The maximum thickness of the second copper layer within the measurement object range is T C2MAX and the minimum layer thickness is T C2MIN When 0.5mm≦T P ≦2.0mm, meet 6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26, and 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0.

[0016] The cladding material of the present invention is preferably such that the AC impedance value of a sample with a width of 15 mm is measured by a four-terminal pair method with a distance between voltage electrodes set to 90 mm under room temperature, and the AC volume resistivity obtained by using the AC impedance value when the frequency of the AC current is set to 10 kHz is 20 mΩ·mm or less. In addition, in the present invention, for convenience, the calculated value obtained by dividing the product of the AC impedance value and the cross-sectional area of ​​the sample for measurement (thickness × width of the sample for measurement) by the distance between the voltage electrodes when the AC impedance value is measured is called the AC volume resistivity. In addition, the AC impedance value is set to the following value, that is, a sample with a width of 15 mm (for example, a length of 150 mm) is placed in an environment of room temperature (for example, above 20°C and below 30°C), and the value (average value) obtained by measuring it at a specified frequency using an inductance (L)-capacitance (C)-impedance (Z) tester by a four-terminal pair method with a distance between voltage electrodes set to 90 mm.

[0017] The cladding material of the present invention is preferably an AC volume resistivity of 200 mΩ·mm or less, when the AC impedance value of a sample with a width of 15 mm is measured by a four-terminal pair method with the distance between voltage electrodes set to 90 mm under room temperature and the AC impedance value is used to determine the AC volume resistivity when the frequency of the AC current is set to 100 kHz.

[0018] The cladding material of the present invention is preferably that the aluminum layer comprises: an aluminum alloy of the JIS specification A3000 series containing Mn (for example, A3003), an aluminum alloy of the JIS specification A5000 series containing Mg (for example, A5052), or an aluminum alloy of the JIS specification A6000 series containing Mg and Si (for example, A6063).

[0019] The clad material of the present invention can be manufactured, for example, by the following method. That is, the manufacturing method of the clad material of the present invention is a manufacturing method of the clad material comprising a preparation step of a clad raw material and a rolling step of the clad material, and in the preparation step of the clad raw material, the following first copper plate, aluminum plate and second copper plate are prepared: assuming that the average plate thickness of the first copper plate is T CS1 and Vickers hardness is B CS1 , the average thickness of the aluminum plate is T AS and Vickers hardness is B AS The average thickness of the second copper plate is T CS2 and Vickers hardness is B CS2 When 6≦T AS / T CS1 ≦26 and 6≦T AS / T CS2 ≦26, and meets B AS / B CS1 ≧1.0 and B AS / B CS2 ≧1.0, in the rolling process of the clad material, the Vickers hardness of the first copper layer corresponding to the first copper plate after rolling is set to B C1 The Vickers hardness of the aluminum layer corresponding to the rolled aluminum plate is B A The Vickers hardness of the second copper layer corresponding to the second copper plate after rolling is B C2 When B is satisfied A / B C1 ≧0.5 and B A / B C2 ≧0.5, rolling the first copper plate, the aluminum plate and the second copper plate prepared in the preparation process of the cladding raw material in a state of being stacked in this order to form a cladding material in which the first copper layer, the aluminum layer and the second copper layer are stacked and pressed in this order, and the manufacturing method of the cladding material constitutes the following cladding material: assuming that the average total thickness of the cladding material is T PThe average thickness of the aluminum layer is T A , the average thickness of the first copper layer is T C1 , the average layer thickness T C1 The maximum thickness of the first copper layer within the measurement object range is T C1MAX and the minimum layer thickness is T C1MIN , the average thickness of the second copper layer is T C2 , the average layer thickness T C2 The maximum thickness of the second copper layer within the measurement object range is T C2MAX and the minimum layer thickness is T C2MIN When 0.5mm≦T P ≦2.0mm, meet 6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26, and 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0.

[0020] The method for producing a clad material of the present invention is preferably such that, in the rolling step of the clad material, 1.0≦T C1MAX / T C1MIN ≦2.5 and 1.0≦T C2MAX / T C2MIN The rolling is performed in a manner of ≦2.5 to form a clad material in which the first copper layer, the aluminum layer, and the second copper layer are stacked and pressed in this order.

[0021] The manufacturing method of the cladding material of the present invention is preferably that the aluminum plate includes: an aluminum alloy of the JIS specification A3000 series containing Mn (for example, A3003), an aluminum alloy of the JIS specification A5000 series containing Mg (for example, A5052), or an aluminum alloy of the JIS specification A6000 series containing Mg and Si (for example, A6063).

[0022] Effects of the Invention

[0023] Through the present invention, a cladding material with a three-layer structure (copper layer-aluminum layer-copper layer) and a method for manufacturing the cladding material can be provided, which can suppress the resistance to a small level while achieving a weight reduction of more than 50% (preferably more than 55%) compared to pure copper material (C1020). In addition, a cladding material suitable for a conductor for alternating current and a method for manufacturing the cladding material can be provided. This can, for example, help reduce the load on electrical or electronic equipment such as vehicle-mounted devices, portable communication equipment, portable chargers or wireless power supplies when they are carried or moved. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] [ Figure 1 ] is a diagram showing a structural example of the cladding material of the present invention.

[0025] [ Figure 2 ] is a diagram showing an example of a cross-sectional structure when the cladding material of the present invention is cut along the thickness direction.

[0026] [ Figure 3 ] is a diagram showing an example of the morphology of undulations produced in the copper layer of the cladding material.

[0027] [ Figure 4 ] is a diagram shown to illustrate the method for producing the cladding material of the present invention.

[0028] [ Figure 5 ] is a graph showing the relationship between the hardness ratio of the copper plate and the aluminum plate of the cladding material and the ripple value of the copper layer of the cladding material.

[0029] [ Figure 6 ](a) is a graph showing the relationship between the ratio of the layer thickness of the copper layer and the aluminum layer of the cladding material and the fluctuation value of the copper layer of the cladding material. (b) is a graph showing the relationship between the ratio of the layer thickness of the copper layer and the aluminum layer of the cladding material whose material of the aluminum layer is equivalent to A5052 and the fluctuation value of the copper layer of the cladding material.

[0030] [ Figure 7 ](a) is a graph showing the relationship between the total thickness of the cladding material and the fluctuation value of the copper layer of the cladding material. (b) is a graph showing the relationship between the layer thickness of the copper layer of the cladding material and the fluctuation value of the copper layer of the cladding material. (c) is a graph showing the relationship between the layer thickness of the aluminum layer of the cladding material and the fluctuation value of the copper layer of the cladding material. DETAILED DESCRIPTION

[0031] The cladding material of the present invention is described by listing an example of its embodiment and appropriately referring to the drawings. In addition, the cladding material of the present invention is not limited to the structure exemplified here, but is represented by the claims, which are equivalent to clarifying that all changes within the meaning and scope equivalent to the claims are included.

[0032] Figure 1 The structural examples of the cladding material of the present invention are shown in FIG. Figure 2 hereinafter shows an example of a cross-sectional structure when the cladding material of the present invention is cut along the thickness direction. Figure 1 and Figure 2 In the figure, X is the crimping direction (rolling direction) of the clad material 1, and Z is the laminating direction (thickness direction) of the clad material 1. Figure 2 The cross-sectional portion of the cladding material 1 shown corresponds to the average layer thickness T of the copper layer 11 and the copper layer 12. C1 , average layer thickness T C2The measurement object range.

[0033] The cladding material 1 is a cladding material having a three-layer structure (copper layer-aluminum layer-copper layer) in which a copper layer 11 as a first copper layer, an aluminum layer 13, and a copper layer 12 as a second copper layer are mainly composed. In addition, depending on the application of the cladding material 1, for example, an insulating or conductive resin layer or a highly corrosion-resistant metal layer (Ni plating layer, etc.) may be provided on a part or all of the surfaces (XY plane) of the copper layers 11 and 12, and on a part or all of the end faces (XZ plane or YZ plane) of the cladding material 1 where the aluminum layer 13 is exposed and intersecting with the thickness direction (Z direction).

[0034] The clad material 1 has a diffusion layer 14a between the copper layer 11 and the aluminum layer 13, and a diffusion layer 14b between the copper layer 12 and the aluminum layer 13, in addition to the above-mentioned main layer. The diffusion layers 14a and 14b are visible as continuous or discontinuous thin layers in the cross section (XZ plane) in the thickness direction (Z direction) of the clad material 1, and are not thick layers like the copper layer 11, the copper layer 12 or the aluminum layer 13 as the main layer. In addition, the average thickness of the diffusion layers 14a and 14b in the clad material 1 is not less than 1 μm and not more than 5 μm. Therefore, the diffusion layers 14a and 14b do not substantially affect the conductivity (resistance) of the clad material 1. If the average thickness of the diffusion layers 14a and 14b exceeds 5 μm, cracks are likely to occur starting from the intermetallic compounds present in the diffusion layers 14a and 14b, and the bonding strength between the copper layers 11 and 12 and the aluminum layer 13 is likely to decrease.

[0035] The clad material 1 is formed by laminating and pressing the copper layer 11, the aluminum layer 13, and the copper layer 12 in this order. The laminating and pressing of the copper layer 11, the aluminum layer 13, and the copper layer 12 can be performed by a specific manufacturing method of the clad material described later. The clad material 1 immediately after laminating and pressing can have the following characteristics: Figure 1 and Figure 2 The flat plate-like form shown in FIG. Such a flat plate-like cladding material 1 can be processed into a desired shape according to the application. In addition, the cladding material formed by lamination and crimping can have the above-mentioned diffusion layer 14a and diffusion layer 14b by performing a heat treatment (diffusion annealing) to produce element diffusion. The cladding material 1 having a moderate thickness of the diffusion layer 14a and diffusion layer 14b can be made into a cladding material 1 with a greater bonding strength between the main layers.

[0036] The cladding material 1 is Figure 1 and Figure 2 In the flat plate shape shown, assuming that the average total thickness is T P The average thickness of the aluminum layer 13 is T A (>0), the average thickness of the copper layer 11 is T C1 (>0), average layer thickness TC1 The maximum thickness of the copper layer 11 within the measurement target range is T C1MAX (>0) and the minimum layer thickness is T C1MIN (>0), the average thickness of the copper layer 12 is T C2 (>0), average layer thickness T C2 The maximum thickness of the copper layer 12 within the measurement target range is T C2MAX (>0) and the minimum layer thickness is T C2MIN (>0), satisfied

[0037] (1) 0.5mm≦T P ≦2.0mm,

[0038] (2)6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26,

[0039] (3)1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0.

[0040] (1) 0.5mm≦T P ≦2.0mm

[0041] Meet 0.5mm≦T P Average total thickness T of the cladding material 1 ≤ 2.0 mm P The average total thickness T is 0.5 mm or more and 2.0 mm or less. P When the cladding material 1 is 0.5 mm or more and 2.0 mm or less, for example, it is used as a conductor in a mobile or portable electric current device, which is advantageous for achieving lightweight while ensuring the electrical characteristics of the electric current device. P Less than 0.5mm(T P The thickness of the cladding material is small (<0.5 mm), and the weight is reduced accordingly, so it is beneficial for lightweighting. However, the mechanical strength is reduced accordingly due to the small thickness, so it is disadvantageous in practical use. Specifically, the cladding material with too small thickness is easy to deform during its handling, and it is easy to cause damage when the current device incorporating the cladding material is subjected to impact or vibration. In addition, the average total thickness T P More than 2.0mm(T P The cladding material with a thickness of 2.0 mm or more has a large thickness, and the mechanical strength is improved accordingly, so it is advantageous in practical use. However, the weight increases accordingly due to the large thickness, so it is not conducive to lightweighting. P The determination method will be described later.

[0042] (2)6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26

[0043] Satisfy 6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26 cladding material and meet T A / T C1 Compared with the cladding material of <6, the total layer thickness of the copper layer (T C1 +T C2 ) is the thickness of the aluminum layer (T A ) becomes larger, so the proportion of copper in the cladding material can be reduced. By further reducing the proportion of copper in the cladding material and relatively increasing the proportion of aluminum, it becomes easier to reduce the weight of the cladding material by more than 50% compared with pure copper material (equivalent to C1020) or reduce the total cost involved in the manufacture of the cladding material. It is preferred to further increase the proportion of aluminum in the cladding material. For example, satisfying 8≦T A / T C1 ≦26 and 8≦T A / T C2 Cladding materials with a weight of ≤26 can be expected to be 55% or more lighter than pure copper materials (equivalent to C1020). In addition, if the total cost of cladding materials is reduced, cheaper cladding materials can be provided. Regarding the total cost of cladding materials, for example, based on the average benchmark of the three-month futures settlement value of the London Metal Exchange in May 2023, the price of copper is about 3.6 times that of aluminum (raw aluminum).

[0044] About meeting 6≦T A / T C1 ≦26 cladding material 1, due to T A >0 and T C1 >0, so 6·T C1 ≦T A ≦26·T C1 Therefore, when 6≦T A / T C1 In the cladding material 1 of ≤26, the average thickness T of the aluminum layer 13 A is the average layer thickness T of the copper layer 11 C1 6 times or more and 26 times or less. Similarly, for the case where 6≦T A / T C2 ≦26 cladding material 1, due to T A >0 and T C2 >0, so 6·TC2 ≦T A ≦26·T C2 Therefore, when 6≦T A / T C2 In the cladding material 1 of ≤26, the average thickness T of the aluminum layer 13 A is the average layer thickness T of the copper layer 12 C2 Therefore, the thickness ratio of the main layer constituting the cladding material 1 (hereinafter, T C1 :T A :T C2 In the form of T C1 =T C2 (>0), for example, if T C1 =1, then T C1 :T A :T C2 =1:6:1~1:26:1. In addition, in T C1 ≠T C2 (>0), for example, if T C1 =1, T C2 = m·T C1 (m>0), then T C1 :T A :T C2 =1:6:m~1:26:m. In addition, T A / T C1 and T A / T C2 Set to the value after rounding off the first decimal place.

[0045] In the cladding material 1, when 0.5 mm ≤ T P ≦2.0mm, and meet 6≦T A / T C1 ≦26 and 6≦T A / T C2 When ≤26, the sum of the average thickness of each layer (T C1 +T A +T C2 ) and the average total thickness T P That is, it can be considered that in the cladding material 1, T P =T C1 +T A +T C2 Established. According to the T P =T C1 +T A +T C2 The relationship between T C1 =T C2 (>0), as mentioned above, due to TC1 :T A :T C2 =1:6:1~1:26:1, so T P = (1+6+1)·T C1 Above and (1+26+1)·T C1 Below, that is, 8·T C1 Above and 28·T C1 In addition, in T C1 ≠T C2 (>0), as mentioned above, due to T C1 :T A :T C2 =1:6:m~1:26:m(T C2 = m·T C1 , m>0), so T P = (1+6+m)·T C1 Above and (1+26+m)·T C1 Below, that is, (7+m)·T C1 Above and (27+m)·T C1 the following.

[0046] Furthermore, as mentioned above, the average total thickness T of the cladding material 1 is P is greater than 0.5 mm and less than 2.0 mm, so at T C1 =T C2 (>0), T P 8·T C1 Above and 28·T C1 The following with T P Therefore, the average thickness T of the copper layer 11 is 0.5 mm or more and 2.0 mm or less. C1 The average thickness T of the copper layer 12 is 1 / 28×0.5 mm or more and 1 / 8×2.0 mm or less, that is, approximately 0.018 mm or more and 0.25 mm or less. C2 The average thickness T of the aluminum layer 13 is 1 / 28×0.5 mm or more and 1 / 8×2.0 mm or less, that is, approximately 0.018 mm or more and 0.25 mm or less. A Available T P -(T C1 +T C2 ) is obtained, so it is generally greater than 0.46 mm and less than 1.50 mm. On the other hand, at T C1 ≠T C2 (T C2 = m·T C1 , m>0), T P = (7+m)·T C1Above and (27+m)·T C1 The following with T P Therefore, the average thickness T of the copper layer 11 is 0.5 mm or more and 2.0 mm or less. C1 is greater than or equal to 1 / (27+m)×0.5 mm and less than or equal to 1 / (7+m)×2.0 mm. C2 T C2 = m·T C1 , so it is m / (27+m)×0.5mm or more and m / (7+m)×2.0mm or less. In addition, m=1 means T C1 =T C2 (>0) About the average layer thickness T of the cladding material 1 A , average layer thickness T C1 and average layer thickness T C2 The determination method will be described later.

[0047] (3)1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0

[0048] Satisfy 1.0≦T C1MAX / T C1MIN In the clad material 1 with a value T of ≦3.0, the variation (deviation) of the thickness of the copper layer 11 measured at a plurality of locations along the rolling direction (X direction) of the clad material 1 is suppressed to be small. C1 The maximum layer thickness T of the copper layer 11 within the measurement target range C1MAX and minimum layer thickness T C1MIN The maximum layer thickness T C1MAX Divide by the minimum layer thickness T C1MIN The clad material 1 having a value of 3.0 or less has the copper layer 11 formed uniformly along the rolling direction (X direction). Preferably, the clad material 1 having a value of 3.0 or less has the copper layer 11 formed uniformly along the rolling direction (X direction). C1MAX / T C1MIN The copper layer 11 is preferably formed sufficiently uniformly to satisfy 1.0≦T C1MAX / T C1MIN ≦2.0 copper layer 11.

[0049] In addition, satisfying 1.0≦T C2MAX / T C2MIN In the clad material 1 with a value T of ≦3.0, the variation (deviation) of the thickness of the copper layer 12 measured at a plurality of locations along the rolling direction (X direction) of the clad material 1 is suppressed to be small. C2The maximum layer thickness T of the copper layer 12 within the measurement target range C2MAX and minimum layer thickness T C2MIN The maximum layer thickness T C2MAX Divide by the minimum layer thickness T C2MIN The clad material 1 having a value of 3.0 or less has the copper layer 12 formed uniformly along the rolling direction (X direction). Preferably, the clad material 1 having a value of 3.0 or less has the copper layer 12 formed uniformly along the rolling direction (X direction). C2MAX / T C2MIN The copper layer 12 is preferably formed sufficiently uniformly to satisfy 1.0≦T C2MAX / T C2MIN ≦2.0 copper layer 12.

[0050] In the cladding material 1 having a three-layer structure (copper layer 11 - aluminum layer 13 - copper layer 12), the variation in the thickness of the outermost copper layer 11 and copper layer 12 is called fluctuation. C1 The maximum layer thickness T within the measurement object range C1MAX Divide by the minimum layer thickness T C1MIN The obtained T C1MAX / T C1MIN The value of is called the fluctuation value of copper layer 11. C1MAX ≧T C1MIN , so the fluctuation value of the copper layer 11 becomes greater than 1.0. Similarly, the average layer thickness T of the copper layer 12 is C2 The maximum layer thickness T within the measurement object range C2MAX Divide by the minimum layer thickness T C2MIN The obtained T C2MAX / T C2MIN The value of is called the fluctuation value of copper layer 12. C2MAX ≧T C2MIN , so the fluctuation value of the copper layer 12 becomes greater than 1.0. Regarding the maximum layer thickness T of the copper layer 11 and the copper layer 12 of the cladding material 1 C1MAX , maximum layer thickness T C2MAX and minimum layer thickness T C1MIN , minimum layer thickness T C2MIN The determination method will be described later.

[0051] Here, Figure 3 2 shows an example of the morphology of undulations generated in the copper layer of the cladding material (cross-sectional photograph). Figure 3 The cross-sectional photographs shown are photographs of the cross-section of the clad material taken along the rolling direction (X direction) at the same magnification. Figure 3 The cladding material shown in (a) has a three-layer structure (copper layer-aluminum layer-copper layer) of C1020 / A1050 / C1020 (refer to Figure 2 ), and the total thickness T P1.0mm, layer thickness T C1 , layer thickness T A , layer thickness T C2 The ratio is 1:4:1. The undulation of the copper layer can be clearly seen near the center of the cross-sectional photograph. Figure 3 The cladding material shown in (b) has a three-layer structure (copper layer-aluminum layer-copper layer) of C1020 / A5052 / C1020 (refer to Figure 2 ), total thickness T P 1.7mm, layer thickness T C1 , layer thickness T A , layer thickness T C2 The ratio is 1:23:1. In the cross-sectional photograph, the undulation of the copper layer cannot be clearly seen.

[0052] As described above, in the cladding material 1, the undulations of the copper layers 11 and 12 satisfy 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0 is suppressed to a small extent, so when manufacturing the clad material, a part of the aluminum layer 13 is not easily exposed to the surface of the clad material 1. In addition, as described above, in the clad material 1, T C1 :T A :T C2 is 1:6:m to 1:26:m (m>0), and is 1:6:1 to 1:26:1 (m=1), so regarding the thickness ratio (X) of the aluminum layer described in the problem to be solved by the invention, 6≦X≦26 holds, thereby satisfying X≧5. Therefore, the cladding material 1 can sufficiently increase the average layer thickness T of the aluminum layer 13 A The average layer thickness T of the copper layer 11 and the copper layer 12 is C1 , average layer thickness T C2 ratio.

[0053] Thus, even the aluminum layer 13 composed of A1050 which is easily exposed on the surface of the cladding material 1 can be sufficiently increased in average layer thickness T A The ratio of , can also fully suppress the exposure to the surface of the cladding material 1. Moreover, by replacing the existing pure copper material containing C1020 with a cladding material 1 that satisfies the above (1), (2), and (3), for example, a copper layer containing C1020, an aluminum layer containing A1050, and a copper layer containing C1020 stacked and pressed in this order, it is possible to achieve a weight reduction of 50% or more compared to the pure copper material. In addition, from the perspective of lightweighting the cladding material 1, the T of the cladding material 1 is C1 :T A :T C2 It is preferably close to 1:26:1, and it is preferred to make TA Relative to T C1 、T C2 The ratio of the aluminum layer to the copper layer can be increased by changing the range of 1:6:1 to 1:7:1, 1:8:1 or 1:9:1, for example.

[0054] In addition, the material of the aluminum layer 13 constituting the cladding material 1 is not limited to the above-mentioned A1050 (1000 series aluminum of JIS standard). The material of the aluminum layer 13 constituting the cladding material 1 may be, for example, an aluminum alloy of the A3000 series of the JIS standard containing Mn (for example, A3003), an aluminum alloy of the A5000 series of the JIS standard containing Mg (for example, A5052), or an aluminum alloy of the A6000 series of the JIS standard containing Mg and Si (for example, A6063). In addition, in order to suppress the undulation of the copper layers 11 and 12 constituting the cladding material 1, it is preferable to increase the deformation resistance of the aluminum layer 13 so as to make it close to the deformation resistance of the copper layers 11 and 12. Regarding the room temperature deformation resistance of aluminum alloy, for example, referring to Non-Patent Document 1 (Fig. 7, the case of strain 0.4), A3003 is about 1.7 times, A6063 is about 2.24 times, and A5052 is about 2.46 times relative to A1050. Therefore, it can be considered that the material of the aluminum layer 13 is preferably A3003 or A3000 series, more preferably A6063 or A6000 series, and further preferably A5052 or A5000 series.

[0055] Here, try to consider the case where the cladding material of the three-layer structure (copper layer-aluminum layer-copper layer) is used as a conductor used in a current device for alternating current, such as a portable charger or a wireless power supply. In the case of alternating current, the skin effect of the conductor sometimes becomes a problem depending on the frequency used. The skin depth of the conductor depends on the material (conductivity, magnetic permeability) of the conductor and the frequency of the alternating current, so it will not change even if the cross-sectional area of ​​the conductor is simply increased. Moreover, it is easy for current to flow in copper, which has high conductivity and low resistance compared to aluminum. Therefore, it can be considered that the actual effective cross-sectional area of ​​the cladding material for flowing alternating current will not change even if the total thickness of the cladding material is simply increased, but depends on the cross-sectional area of ​​the copper layer constituting the surface and back of the cladding material. From this point of view, the smaller the fluctuation value of the copper layer constituting the cladding material, the larger the apparent cross-sectional area of ​​the central part in the thickness direction (Z direction) of the copper layer, thereby ensuring the actual effective cross-sectional area of ​​the copper layer, so that the resistance of the cladding material can be suppressed to a small level.

[0056] The skin depth of a conductor for alternating current, for example, in the case of a conductor made of pure copper (equivalent to C1020) in an environment of about 20°C is approximately: about 9.3 mm at 50 Hz, about 8.5 mm at 60 Hz, about 2.1 mm at 1 kHz, about 0.66 mm at 10 kHz, about 0.30 mm at 50 kHz, about 0.25 mm at 70 kHz, about 0.21 mm at 100 kHz, about 0.20 mm at 110 kHz, about 0.18 mm at 130 kHz, about 0.09 mm at 500 kHz, about 0.079 mm at 700 kHz, about 0.07 mm at 1 MHz, about 0.02 mm at 10 MHz, about 0.018 mm at 13 MHz, and about 0.006 mm at 120 MHz.

[0057] For example, T P is 0.5 mm and has a T C1 、T C2 The T of the cladding material 1 including the copper layer 11 and the copper layer 12 of pure copper (C1020) of 0.018 mm C1 :T A :T C2 It is approximately 1:26:1. When the cladding material 1 is used as a conductor for alternating current, if there is no undulation in the copper layer 11, the copper layer 12 (undulation value = 1.0), it is considered that it is not easily affected by the aluminum layer 13 having a greater resistance (conductivity) than the copper layer 11, the copper layer 12, and it is preferably used at a frequency (about 13MHz) or more that makes the skin depth 0.018mm or less. In addition, even if there is undulation in the copper layer 11, the copper layer 12, if the undulation value does not exceed 3.0, the minimum layer thickness T of the copper layer 11, the copper layer 12 is C1MIN , minimum layer thickness T C2MIN Also the average layer thickness T C1 , average layer thickness T C2 1 / 3 (about 0.006 mm) or more, so it is considered that it is preferably used at a frequency (about 120 MHz) or more that makes the skin depth 0.006 mm or less. Similarly, if the fluctuation value of the copper layer 11 and the copper layer 12 is, for example, 2.5, it is considered that it is preferably used at a frequency (about 85 MHz) or more that makes the skin depth 0.007 mm or less, and if it is, for example, 2.0, it is considered that it is preferably used at a frequency (about 55 MHz) or more that makes the skin depth 0.009 mm or less.

[0058] For example, T P is 2.0 mm and has a T C1 、T C2 The T of the cladding material 1 including the copper layer 11 and the copper layer 12 of pure copper (C1020) of 0.25 mm C1 :T A :T C2It is approximately 1:6:1. When the cladding material 1 is used as a conductor for alternating current, if there is no fluctuation in the copper layer 11, the copper layer 12 (the fluctuation value = 1.0), it is considered that it is not easily affected by the aluminum layer 13 having a greater resistance (conductivity) than the copper layer 11, the copper layer 12, and it is preferably used at 70kHz or more so that the skin depth is less than 0.25mm. In addition, even if there is fluctuation in the copper layer 11, the copper layer 12, if the fluctuation value does not exceed 3.0, the minimum layer thickness T of the copper layer 11, the copper layer 12 is C1MIN , minimum layer thickness T C2MIN Also the average layer thickness T C1 , average layer thickness T C2 1 / 3 (about 0.083 mm) or more, so it is considered that it is preferably used at a frequency (about 700 kHz) or more that makes the skin depth 0.079 mm or less. Similarly, if the fluctuation value of the copper layer 11 and the copper layer 12 is, for example, 2.5, it is considered that it is preferably used at a frequency (about 440 kMHz) or more that makes the skin depth 0.10 mm or less, and if it is, for example, 2.0, it is considered that it is preferably used at a frequency (about 280 kHz) or more that makes the skin depth 0.125 mm or less.

[0059] As described above, when the clad material 1 is used as a conductor for alternating current in consideration of the skin depth, it is considered that there is a range of frequencies suitable for use corresponding to the fluctuation values ​​of the copper layers 11 and 12 of the clad material. However, as described later, the clad material 1 satisfying the above (1), (2), and (3) has an AC volume resistivity of 20 mΩ·mm or less when the frequency of the alternating current is set to 10 kHz, and an AC volume resistivity of 200 mΩ·mm or less when the frequency of the alternating current is set to 100 kHz. From this viewpoint, the clad material 1 satisfying the above (1), (2), and (3) can fully function as a conductor for alternating current having a frequency of 10 kHz or more and 100 kHz or less.

[0060] The copper layers 11 and 12 constituting the cladding material 1 are preferably made of pure copper such as C1020 or C1100 of the JIS standard having low resistance and excellent conductivity, if it is considered that they are used as conductors regardless of direct current or alternating current. Conventionally, most pure copper materials used as conductors regardless of direct current or alternating current include C1020 or C1100, and their conductivity is about 100% IACS.

[0061] Regarding the aluminum layer 13 constituting the cladding material 1, it is considered that it is preferable to include pure aluminum such as A1050 or A1100 of the JIS specification having a lower electrical resistance. However, when a cladding material having a large thickness ratio of the aluminum layer relative to the copper layer is manufactured by using a copper plate containing C1020 and an aluminum plate containing A1050 by an existing cladding material manufacturing method, the ripple value of the copper layer sometimes exceeds 3.0 and does not satisfy the above (3). The reason is that when the copper plate containing C1020 and the aluminum plate containing A1050 are stacked and pressed, even if the copper plate containing C1020 is tempered to be sufficiently softened, and the aluminum plate containing A1050 is tempered to be as hard as possible, the difference in deformation resistance generated between the copper plate and the aluminum plate when they are stacked and pressed together still becomes too large.

[0062] Therefore, the aluminum layer 13 constituting the cladding material 1 preferably includes an aluminum alloy having a relatively low electrical resistance and capable of being tempered and hardened accordingly. From this viewpoint, the aluminum alloy combined with pure copper having a high electrical conductivity and an advantage such as C1020 is preferably an A3000 series aluminum alloy containing Mn according to JIS standards such as A3003, an A5000 series aluminum alloy containing Mg according to JIS standards such as A5052, or an A6000 series aluminum alloy containing Mg and Si according to JIS standards such as A6063. By using the above-mentioned aluminum alloys such as A3003, A5052 or A6063, the difference in deformation resistance can be suppressed to a small value when laminating and crimping with pure copper. In addition, the electrical conductivity is, for example, about 101% IACS for C1020, about 60% IACS for A1050, about 40% IACS (temper H18) to about 50% IACS (temper O) for A3003, about 35% IACS (average of all tempers) for A5052, and about 53% IACS (temper T6) to about 58% IACS (temper O) for A6063. In addition, the specific gravity is, for example, about 8.94 for C1020, about 2.70 for A1050, about 2.73 for A3003, about 2.68 for A5052, and about 2.61 for A6063.

[0063] In order to stably and easily manufacture the above Figure 1 and Figure 2 The cladding material 1 shown in the figure requires some design in the existing cladding material manufacturing method. That is, the cladding material manufacturing method of the present invention is as follows Figure 4 Shown, including

[0064] (A) Preparation of cladding material, and

[0065] (B) Rolling process of cladding material,

[0066] Some designs are performed in each of the steps (A) and (B).

[0067] (A) Preparation process of cladding materials

[0068] In manufacturing Figure 1 and Figure 2 In the case of the cladding material 1 shown in the figure, in the cladding material preparation step, a material satisfying 6≦T is prepared. AS / T CS1 ≦26 and 6≦T AS / T CS2 ≦26, and meets B AS / B CS1 ≧1.0 and B AS / B CS2 ≧1.0 first copper plate, aluminum plate and second copper plate. AS / T CS1 and T AS / T CS2 The first copper plate corresponds to the copper layer 11 (first copper layer) constituting the cladding material 1. The aluminum plate corresponds to the aluminum layer 13 constituting the cladding material 1. The second copper plate corresponds to the copper layer 12 (second copper layer) constituting the cladding material 1. CS1 is the average thickness of the first copper plate, and its Vickers hardness is B CS1 . T AS is the average thickness of the aluminum plate, and its Vickers hardness is B AS . T CS2 is the average thickness of the second copper plate, and its Vickers hardness is B CS2 . B CS1 , B AS and B CS2 The clad material (the first copper plate, the aluminum plate, and the second copper plate) can be used and obtained by a hardness measurement method in accordance with JIS.

[0069] By preparing AS / T CS1 ≦26 and 6≦T AS / T CS2 When the first copper plate, the aluminum plate, and the second copper plate with a plate thickness of ≦26 are rolled under appropriate conditions in the rolling process of the clad material, it is easy to form a plate satisfying the above (2), that is, satisfying 6≦T A / T C1 ≦26 and 6≦T A / T C2 The reason is that when the first copper plate, the aluminum plate, and the second copper plate are rolled in a stacked state, each plate is rolled at substantially the same rolling processing rate, so the thickness ratio of the three plates before and after rolling does not substantially change. From the perspective of lightweighting the cladding material 1, it is preferred to prepare a material having a range in which the thickness ratio of the aluminum plate to the copper plate is changed to satisfy 8≦TAS / T CS1 ≦26 and 8≦T AS / T CS2 The first copper plate, the aluminum plate, and the second copper plate having a plate thickness of ≦26 are rolled under appropriate conditions in the rolling process of the clad material to form a structure satisfying 8≦T A / T C1 ≦26 and 8≦T A / T C2 ≦26 of the clad material 1. In addition, the plate thicknesses of the first copper plate, the aluminum plate, and the second copper plate prepared in the clad material preparation step are determined by taking into account the average total thickness T obtained by the clad material rolling step described later. P The cladding material 1 can be selected according to needs.

[0070] In addition, by preparing to be quenched and tempered to meet B AS / B CS1 ≧1.0 and B AS / B CS2 When the first copper plate, the aluminum plate, and the second copper plate with a hardness of ≧1.0 are rolled under appropriate conditions in the rolling process of the clad material, it is easy to form a plate that satisfies the above (3), that is, 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0 cladding material 1. Copper or aluminum plates undergo work hardening during rolling, and the Vickers hardness changes. Compared with aluminum plates, the increase in Vickers hardness of copper plates due to work hardening is greater. Considering the increase in Vickers hardness during the rolling process, it is ideal that the hardness of copper plates and aluminum plates is the same, that is, it satisfies B AS / B CS1 =1.0 and B AS / B CS2 =1.0, but considering mass production, it is preferred to satisfy 1.0≦B AS / B CS2 ≦2.0 and 1.0≦B AS / B CS2 ≦2.0, preferably 1.0≦B AS / B CS2 ≦1.8 and 1.0≦B AS / B CS2 ≦1.8.

[0071] (B) Rolling process of cladding material

[0072] In the rolling process of the clad material, the clad raw material prepared in the preparation process meets B AS / B CS1 ≧1.0 and B AS / BCS2 ≧1.0, preferably 1.0≦B AS / B CS2 ≦2.0 and 1.0≦B AS / B CS2 ≦2.0, preferably 1.0≦B AS / B CS2 ≦1.8 and 1.0≦B AS / B CS2 The first copper plate, aluminum plate and second copper plate of ≤1.8 are stacked in this order to meet B A / B C1 ≧0.5 and B A / B C2 The rolling is performed in a manner of ≧0.5 to form a clad material in which a copper layer (first copper layer), an aluminum layer, and a copper layer (second copper layer) are laminated and press-bonded in this order.

[0073] The rolling process of the clad material includes a process until the clad material 1 is obtained from the clad raw material. The process of obtaining the clad material by laminating and pressing the clad raw materials is called clad rolling. In the clad rolling, the clad material can be rolled to the same thickness as the clad material 1 or not by selecting the rolling rate (processing degree). The clad material that does not reach the thickness of the clad material 1 after the clad rolling is referred to as the clad intermediate material (refer to Figure 4 ) to distinguish it from the clad material 1. In the case where the clad intermediate material is formed by clad rolling, a process is required to roll the clad intermediate material to the thickness of the clad material 1. Therefore, the rolling process of the clad material includes intermediate rolling or finish rolling of the clad intermediate material. In addition, the intermediate rolling is intended to be a rolling process for making the thickness of the clad intermediate material close to the thickness of the clad material 1, or for making the thickness of the clad intermediate material the same as that of the clad material 1. In addition, the finish rolling is intended to be a rolling process for making the thickness of the clad intermediate material the same as that of the clad material 1. The clad material having the same thickness as the clad material 1 can be obtained by any one of clad rolling, a combination of clad rolling and finish rolling, and a combination of clad rolling, intermediate rolling, and finish rolling.

[0074] The rolling rate (processing degree) in clad rolling is preferably selected within the range of more than 40% and less than 80%. If the rolling rate of clad rolling is too small, there is a tendency for the bonding strength between the layers constituting the clad material to become insufficient, and sometimes the copper layer peels off. If the rolling rate of clad rolling is too large, there is a tendency for the undulation of the copper layer constituting the clad material to become larger, and sometimes the undulation value of the copper layer becomes larger. In addition, in the case of intermediate rolling or finish rolling, with respect to its rolling rate, there is a tendency for the undulation of the copper layer to become slightly larger if the total rolling rate (total rolling rate) accumulated from the start of clad rolling becomes larger, so it is preferably selected in consideration of the undulation value of the copper layer.

[0075] By adjusting the hardness ratio (B AS / B CS1 and B AS / B CS2 ) is designed, and then the hardness ratio (B A / B C1 and B A / B C2 ) is designed to easily satisfy the above (3), that is, to satisfy 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0 of cladding material 1. The more the cladding material B AS / B CS1 and B AS / B CS2 The closer it is to 1.0, the easier it is to make the T of the cladding material 1 C1MAX / T C1MIN and T C2MAX / T C2MIN Close to 1.0.

[0076] B C1 , B A and B C2 The clad material obtained by clad rolling can be used and obtained by the hardness measurement method according to JIS. C1 is the Vickers hardness of the copper layer (first copper layer) corresponding to the first copper plate. A is the Vickers hardness of the aluminum layer corresponding to the aluminum plate. C2 It is the Vickers hardness of the copper layer (second copper layer) corresponding to the second copper plate.

[0077] Thus, a clad material having the same thickness as the clad material 1 or a clad intermediate material thicker than the clad material 1 can be obtained. In order to improve the bonding strength between the layers constituting the clad material, the clad material after clad rolling is preferably subjected to a heat treatment (diffusion annealing) for forming a diffusion layer of appropriate thickness. Regarding the diffusion layer, refer to the diffusion layer 14a and the diffusion layer 14b of the clad material 1. In addition, for the clad material after clad rolling or heat treatment (diffusion annealing), a heat treatment process such as softening annealing, a surface treatment process, a slit processing process, etc. can be selectively performed as needed.

[0078] The above-mentioned steps include the preparation process of the clad raw material and the rolling process of the clad material, and the optional process as needed. Figure 4 The manufacturing method of the cladding material shown can constitute Figure 1 and Figure 2 The cladding material 1 shown, namely

[0079] Satisfy (1) 0.5 mm ≤ T P ≦2.0mm,

[0080] Satisfy (2) 6 ≦ T A / T C1 ≦26 and 6≦T A / T C2 ≦26, and

[0081] Satisfy (3) 1.0 ≦ T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.0

[0082] Cladding material 1.

[0083] At this time, the clad material 1 is preferably configured so that the range of the thickness ratio of the aluminum layer to the copper layer is changed so as to satisfy, for example, 8≦T A / T C1 ≦26 and 8≦T A / T C2 ≦26. In addition, the cladding material 1 is preferably configured to satisfy 1.0≦T C1MAX / T C1MIN ≦2.5 and 1.0≦T C2MAX / T C2MIN ≦2.5, and more preferably, 1.0≦T C1MAX / T C1MIN ≦2.0 and 1.0≦T C2MAX / T C2MIN ≦2.0. In addition, in the cladding material 1, it is desirable that T C1MAX / T C1MIN and T C2MAX / TC2MIN is 1.0.

[0084] Example

[0085] Regarding the cladding material and the method for producing the cladding material of the present invention, using Figure 4 The method for manufacturing the cladding material shown in the figure was used to trial manufacture a cladding material having an overlay type three-layer structure (copper layer-aluminum layer-copper layer) as a representative structural example of the cladding material (see Figure 1 and Figure 2 ) and were evaluated. Table 1 shows the clad raw materials (raw material numbers 1 to 23) prepared in the clad raw material preparation process. Table 2 shows the clad materials (sample numbers 1 to 23) formed in the rolling process of the clad materials. In addition, among the trials 1 to 23 shown in Table 2, trials 1 to 13 and trial 23 are examples of the present invention.

[0086] [Table 1]

[0087]

[0088] [Table 2]

[0089]

[0090] In the cladding material preparation process, corresponding to the trials 1 to 23, cladding materials (copper plates, aluminum plates) with material numbers 1 to 23 shown in Table 1 were prepared. In Table 1, the materials of the copper plates (first copper plates, second copper plates) and the aluminum plates correspond to the JIS standards. In addition, the plate thicknesses T of the copper plates (first copper plates, second copper plates) and the aluminum plates are CS1 、Thickness T CS2 And plate thickness T AS It is the measured value (average value) obtained by using a micrometer before cladding rolling. In addition, the Vickers hardness B of the copper plate (first copper plate, second copper plate) and the aluminum plate CS1 , Vickers hardness B CS2 and Vickers hardness B AS It is the measured value (average value) obtained by the Vickers hardness test according to JIS-Z2244 before clad rolling. AS / T CS1 and T AS / T CS2 is the thickness of the aluminum plate T AS Divide by the thickness T of the copper plates (first copper plate, second copper plate) CS1 And plate thickness T CS2 The value is rounded to the first decimal place. AS / B CS1 and B AS / B CS1is the Vickers hardness B of the aluminum plate AS Divide by the Vickers hardness B of the copper plates (first copper plate, second copper plate) CS and Vickers hardness B CS2 And the value is rounded to the second decimal place. In addition, T CS1 +T AS +T CS2 It is the total thickness of three plates when two copper plates (first copper plate and second copper plate) and one aluminum plate are stacked.

[0091] Corresponding to trials 1 to 23, respectively, in the rolling process of the clad material, the prepared clad raw materials (copper plates, aluminum plates) of raw material numbers 1 to 23 are used, and the clad rolling is performed in a manner to achieve the clad rolling rate shown in Table 2, to form the clad materials of the three-layer structure (copper layer-aluminum layer-copper layer) of sample numbers 1 to 23 shown in Table 2. In addition, in any trial, before the clad rolling, one of the plate surfaces of the copper plate and the two plate surfaces of the aluminum plate that are in contact with each other when the three plates are stacked are surface treated by grinding (polishing) with a stainless steel brush. In addition, in any trial, after the clad rolling, a heat treatment (diffusion annealing) is performed in a furnace set to a nitrogen atmosphere based on the specified holding conditions (400°C, 3 minutes).

[0092] In Table 2, for example, C1020 / A5052 / C1020 shown as a layer structure in Sample No. 1 means a cladding material having a three-layer structure (copper layer-aluminum layer-copper layer). P It is the measured value obtained by using a micrometer after clad rolling (the value after rounding off the third decimal place of the average value). In addition, the layer thickness T of the copper layer (first copper layer, second copper layer) and the aluminum layer C1 , layer thickness T C2 and layer thickness T A It is possible to observe the cladding material along the rolling direction ( Figure 1 The measured value of the sample processed by cutting the sample in the manner of a 20 mm long section (in the X direction shown) under a metal microscope (magnification 200 times) (the value after rounding off the third decimal place of the average value). In addition, T A / T C1 and T A / T C2 is the thickness of the aluminum layer T A Divide by the thickness T of the copper layer (first copper layer, second copper layer) C1 and layer thickness T C2 The value is rounded to the first decimal place. In addition, the average layer thickness T of the two copper layers (first copper layer and second copper layer) constituting the cladding material obtained as described above is C1 , average layer thickness T C2 About the same.

[0093] In Table 2, the Vickers hardness B of the copper layer (first copper layer, second copper layer) and the aluminum layer is C1 , Vickers hardness B C2 and Vickers hardness B A This is the measured value (average value) obtained by the Vickers hardness test in accordance with JIS-Z2244 before clad rolling. A / B C1 and B A / B C2 is the Vickers hardness B of the aluminum layer A Divide by the Vickers hardness B of the copper layer (first copper layer, second copper layer) C1 and Vickers hardness B C2 The value is rounded to the second decimal place. In addition, the hardness B of the two copper layers (first copper layer and second copper layer) constituting the front and back of the clad material obtained as described above is C1 , Hardness B C2 About the same.

[0094] In Table 2, the lightweight ratio is expressed by (1-W CLAD / W C1020 )×100. Here, W CLAD is the layer thickness T of the copper layer (first copper layer) C1 ×Specific gravity of copper layer (first copper layer)+Thickness T of aluminum layer A ×Specific gravity of aluminum layer+Thickness of copper layer (second copper layer) T C2 × the specific gravity of the copper layer (second copper layer), and is defined as the weight index of the flat cladding material. C1020 It is a calculated value obtained by multiplying the thickness of the flat plate-shaped pure copper material by the specific gravity of the pure copper material (8.94), and is defined as a weight index of the pure copper material. For the flat plate-shaped pure copper material, the material is set to be equivalent to JIS standard C1020, and its plate thickness is set to be equal to the total thickness T of the cladding material to be evaluated. P The specific gravity of each material is 8.94 for the material corresponding to C1020, 2.70 for the material corresponding to A1050, 2.69 for the material corresponding to A5052, and 2.68 for the material corresponding to A6063.

[0095] In Table 2, the fluctuation value is a calculated value obtained by dividing the maximum layer thickness of the copper layer constituting the cladding material by the minimum layer thickness (rounded off to the second decimal place). C1MAX / T C1MIN 、T C2MAX / T C2MIN) records the fluctuation value (T C1MAX / T C1MIN ) and the fluctuation value (T C2MIN / T C2MIN ) has a larger fluctuation value. In addition, the maximum layer thickness T of the two copper layers (the first copper layer and the second copper layer) C1MAX , maximum layer thickness T C2MAX and minimum layer thickness T C1MIN , minimum layer thickness T C2MIN Assume that after the average layer thickness T of the two copper layers (the first copper layer and the second copper layer) is obtained C1 , average layer thickness T C2 The measured value is determined under a metal microscope (magnification 200 times) within the range of a cross section of the clad material with a length of 20 mm along the rolling direction.

[0096] In Table 2, the presence or absence of surface exposure of the aluminum layer is determined by visually observing the surfaces of the copper layers constituting the front and back of the flat-plate cladding material. The case where exposure of the aluminum portion was confirmed on the surface of the copper layer was expressed as "yes", and the case where exposure of the aluminum portion was not confirmed was expressed as "no".

[0097] In trial production 1 (inventive example), a cladding material of material number 1 was prepared, a cladding material of sample number 1 was formed, and the weight reduction rate, the fluctuation value, and the presence or absence of surface exposure of the aluminum layer were evaluated. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate (first copper plate, second copper plate) to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio (T A / T C1 、T A / T C2) is selected in such a way that the thickness of the copper plate (the first copper plate, the second copper plate) and the aluminum plate is 8. In the cladding material, the total thickness is 1.70 mm, the average thickness of the copper layer (the first copper layer, the second copper layer) is 0.18 mm, and the average thickness of the aluminum layer is 1.35 mm, and the lightweight rate compared with the pure copper material (C1020) is 56%. In the cladding material, the fluctuation value of the copper layer is 1.8, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer (the first copper layer, the second copper layer) of the cladding material is suppressed to a more preferred range of less than 2.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 1 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level. Hereinafter, for the sake of simplicity, the copper plates (first copper plate, second copper plate) are simply referred to as copper plates, and the copper layers (first copper layer, second copper layer) are simply referred to as copper layers.

[0098] In Trial 2 (Example of the present invention), a cladding material of material number 2 was prepared, a cladding material of sample number 2 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 26. In the cladding material, the total thickness is 1.70 mm, the average layer thickness of the copper layer is 0.06 mm, and the average layer thickness of the aluminum layer is 1.58 mm, and the lightweight rate compared with the pure copper material (C1020) is 65%. In the cladding material, the fluctuation value of the copper layer is 3.0, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a range below 3.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 2 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0099] In Trial 3 (Example of the present invention), a cladding material of material number 3 was prepared, a cladding material of sample number 3 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2) is 1.4, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 8. In the cladding material, the total thickness becomes 1.70 mm, the average layer thickness of the copper layer becomes 0.18 mm, and the average layer thickness of the aluminum layer becomes 1.35 mm, and the lightweight rate compared with the pure copper material (C1020) becomes 56%. In the cladding material, the fluctuation value of the copper layer becomes 1.7, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 3 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0100] In Trial 4 (Example of the present invention), a cladding material of material number 4 was prepared, a cladding material of sample number 4 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.4, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 26. In the cladding material, the total thickness becomes 1.70mm, the average layer thickness of the copper layer becomes 0.06mm, and the average layer thickness of the aluminum layer becomes 1.58mm, and the lightweight rate compared with the pure copper material (C1020) becomes 65%. In the cladding material, the fluctuation value of the copper layer becomes 2.6, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 4 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0101] In Trial 5 (Example of the present invention), a cladding material of material number 5 was prepared, a cladding material of sample number 5 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / BCS2 ) is 1.7, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 8. In the cladding material, the total thickness becomes 1.70 mm, the average layer thickness of the copper layer becomes 0.18 mm, and the average layer thickness of the aluminum layer becomes 1.35 mm, and the lightweight rate compared with the pure copper material (C1020) becomes 56%. In the cladding material, the fluctuation value of the copper layer becomes 1.5, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 5 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0102] In Trial 6 (Example of the present invention), a cladding material of material number 6 was prepared, a cladding material of sample number 6 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.7, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 26. In the cladding material, the total thickness becomes 1.70mm, the average layer thickness of the copper layer becomes 0.06mm, and the average layer thickness of the aluminum layer becomes 1.58mm, and the lightweight rate compared with the pure copper material (C1020) becomes 65%. In the cladding material, the fluctuation value of the copper layer becomes 2.3, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to within the preferred range of less than 2.5, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 6 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0103] In Trial 7 (Example of the present invention), a cladding material of material number 7 was prepared, a cladding material of sample number 7 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the thickness of the copper plate and the aluminum plate is 8. In the cladding material, the total thickness is 0.50 mm, the average thickness of the copper layer is 0.05 mm, and the average thickness of the aluminum layer is 0.40 mm, and the lightweight rate compared to the pure copper material (C1020) is 56%. In the cladding material, the fluctuation value of the copper layer is 1.8, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is believed that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 7 can be provided as a cladding material that achieves a lightweight of more than 50% compared to the pure copper material (C1020) while suppressing the resistance to a small level.

[0104] In Trial 8 (Example of the present invention), a cladding material of material number 8 was prepared, a cladding material of sample number 8 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 26. In the cladding material, the total thickness is 0.50 mm, the average layer thickness of the copper layer is 0.02 mm, and the average layer thickness of the aluminum layer is 0.46 mm, and the lightweight rate compared with the pure copper material (C1020) is 65%. In the cladding material, the fluctuation value of the copper layer is 3.0, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to within the range of less than 3.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 8 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0105] In Trial 9 (Example of the present invention), a cladding material of material number 9 was prepared, a cladding material of sample number 9 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.4, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the thickness of the copper plate and the aluminum plate is 8. In the cladding material, the total thickness is 0.50 mm, the average thickness of the copper layer is 0.05 mm, and the average thickness of the aluminum layer is 0.40 mm, and the lightweight rate compared to the pure copper material (C1020) is 56%. In the cladding material, the fluctuation value of the copper layer is 1.7, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is believed that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 9 can be provided as a cladding material that achieves a lightweight of more than 50% compared to the pure copper material (C1020) while suppressing the resistance to a small level.

[0106] In Trial 10 (Example of the present invention), a cladding material of material number 10 was prepared, a cladding material of sample number 10 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.4, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 26. In the cladding material, the total thickness is 0.50 mm, the average layer thickness of the copper layer is 0.02 mm, and the average layer thickness of the aluminum layer is 0.46 mm, and the lightweight rate compared with the pure copper material (C1020) is 65%. In the cladding material, the fluctuation value of the copper layer is 2.6, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to within the range of less than 3.0, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 10 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0107] In Trial 11 (Example of the present invention), a cladding material of material number 11 was prepared, a cladding material of sample number 11 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , BAS / B CS2 ) is 1.7, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate is 8. In the cladding material, the total thickness is 0.50 mm, the average layer thickness of the copper layer is 0.05 mm, and the average layer thickness of the aluminum layer is 0.40 mm, and the lightweight rate compared with the pure copper material (C1020) is 56%. In the cladding material, the fluctuation value of the copper layer is 1.5, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is believed that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 11 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0108] In Trial 12 (Example of the present invention), a cladding material of material number 12 was prepared, a cladding material of sample number 12 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.7, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 26. In the cladding material, the total thickness is 0.50 mm, the average layer thickness of the copper layer is 0.02 mm, and the average layer thickness of the aluminum layer is 0.46 mm, and the lightweight rate compared with the pure copper material (C1020) is 65%. In the cladding material, the fluctuation value of the copper layer is 2.3, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to within the preferred range of less than 2.5, so it is believed that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 12 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0109] In Trial 13 (Example of the present invention), a cladding material of material number 13 was prepared, a cladding material of sample number 13 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / BCS1 , B AS / B CS2 ) is 0.5, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate is 6. In the cladding material, the total thickness is 1.72 mm, the average layer thickness of the copper layer is 0.22 mm, and the average layer thickness of the aluminum layer is 1.29 mm, and the lightweight ratio compared to the pure copper material (C1020) is 52%. In the cladding material, the fluctuation value of the copper layer is 2.3, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to within the preferred range of less than 2.3, so it is considered that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 13 can be provided as a cladding material that achieves a lightweight of more than 50% compared to the pure copper material (C1020) while suppressing the electrical resistance to a small level. In addition, in the cladding material of sample number 13 with a lightweight ratio of 52%, the ratio of the layer thickness of the copper layer to the aluminum layer (T A / T C1 、T A / T C2 ) is 6, and the proportion of aluminum in the cladding material is relatively small. Therefore, in order to achieve further lightness or cheapness of the cladding material, it is preferred to make the ratio of the thickness of the copper layer to the aluminum layer (T A / T C1 、T A / T C2 ) for example, to 7, 8 or 9, etc., to increase the proportion of aluminum.

[0110] In Trial 14 (Comparative Example), a clad material of material number 14 was prepared, a clad material of sample number 14 was formed, and evaluation was performed in the same manner as Trial 1. The clad material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 0.5, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2) is selected in such a way that the plate thickness of the copper plate and the aluminum plate is 13. In the cladding material, the total thickness is 1.72 mm, the average layer thickness of the copper layer is 0.12 mm, and the average layer thickness of the aluminum layer is 1.49 mm, and the lightweight rate compared with the pure copper material (C1020) is 60%. In the cladding material, the fluctuation value of the copper layer is 4.0, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for flowing alternating current cannot be guaranteed.

[0111] As a result, although the cladding material of sample number 14 achieved a weight reduction of more than 50% compared to the pure copper material (C1020), there was a possibility that the resistance would increase, and it was confirmed that the surface of the aluminum layer was exposed, so it was confirmed that it could not be provided as a good product. In addition, in trial 14, C1020 and A1050, which are the same materials as trial 13, were combined, but the undulation of the copper layer of the cladding material in trial 13 became smaller. This is believed to be caused by the T of trial 14. A / T C1 and T A / T C2 It is significantly larger than the prototype 13. Therefore, even if the structure is a combination of C1020 and A1050, by A / T C1 and T A / T C2 By setting it in an appropriate range (preferably 6 or more and 10 or less), it can be provided as a good product.

[0112] In Trial 15 (Comparative Example), a cladding material of material number 15 was prepared, a cladding material of sample number 15 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2) becomes 30. In the cladding material, the total thickness becomes 1.68mm, the average thickness of the copper layer becomes 0.05mm, and the average thickness of the aluminum layer becomes 1.58mm, and the lightweight rate compared with the pure copper material (C1020) becomes 66%. In the cladding material, the fluctuation value of the copper layer becomes 4.0, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 15 achieves a lightweight of more than 50% compared with the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0113] In Trial 16 (Comparative Example), a clad material of material number 16 was prepared, a clad material of sample number 16 was formed, and evaluation was performed in the same manner as in Trial 1. The clad material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.4, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) becomes 30. In the cladding material, the total thickness becomes 1.68mm, the average thickness of the copper layer becomes 0.05mm, and the average thickness of the aluminum layer becomes 1.58mm, and the lightweight rate compared with the pure copper material (C1020) becomes 66%. In the cladding material, the fluctuation value of the copper layer becomes 3.8, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 16 achieves a lightweight of more than 50% compared with the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0114] In Trial 17 (Comparative Example), a clad material of material number 17 was prepared, a clad material of sample number 17 was formed, and evaluation was performed in the same manner as in Trial 1. The clad material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.7, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / TC1 、T A / T C2 ) becomes 30. In the cladding material, the total thickness becomes 1.68mm, the average thickness of the copper layer becomes 0.05mm, and the average thickness of the aluminum layer becomes 1.58mm, and the lightweight rate compared with the pure copper material (C1020) becomes 66%. In the cladding material, the fluctuation value of the copper layer becomes 3.7, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 17 achieves a lightweight of more than 50% compared with the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0115] In Trial 18 (Comparative Example), a clad material of material number 18 was prepared, a clad material of sample number 18 was formed, and evaluation was performed in the same manner as Trial 1. The clad material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) becomes 30. In the cladding material, the total thickness is 0.51 mm, the average thickness of the copper layer is 0.02 mm, and the average thickness of the aluminum layer is 0.48 mm, and the lightweight rate compared to the pure copper material (C1020) is 66%. In the cladding material, the fluctuation value of the copper layer is 4.0, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 18 achieves a lightweight of more than 50% compared to the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0116] In Trial 19 (Comparative Example), a cladding material of material number 19 was prepared, a cladding material of sample number 19 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2) is 1.4, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) becomes 30. In the cladding material, the total thickness is 0.51 mm, the average thickness of the copper layer is 0.02 mm, and the average thickness of the aluminum layer is 0.48 mm, and the lightweight rate compared to the pure copper material (C1020) is 66%. In the cladding material, the fluctuation value of the copper layer is 3.8, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 19 achieves a lightweight of more than 50% compared to the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0117] In Trial 20 (Comparative Example), a cladding material of material number 20 was prepared, a cladding material of sample number 20 was formed, and evaluation was performed in the same manner as Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.7, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the thickness of the copper plate and the aluminum plate is 30. In the cladding material, the total thickness is 0.51 mm, the average thickness of the copper layer is 0.02 mm, and the average thickness of the aluminum layer is 0.48 mm, and the lightweight rate compared with the pure copper material (C1020) is 66%. In the cladding material, the fluctuation value of the copper layer is 3.7, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 20 achieves a lightweight of more than 50% compared with the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0118] In Trial 21 (Comparative Example), a cladding material of material number 21 was prepared, a cladding material of sample number 21 was formed, and evaluation was performed in the same manner as Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / BCS1 , B AS / B CS2 ) is 1.3, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) becomes 30. In the cladding material, the total thickness becomes 1.68mm, the average thickness of the copper layer becomes 0.05mm, and the average thickness of the aluminum layer becomes 1.58mm, and the lightweight rate compared with the pure copper material (C1020) becomes 66%. In the cladding material, the fluctuation value of the copper layer becomes 5.5, and it is confirmed that the surface of the aluminum layer is exposed. The fluctuation value of the copper layer of the cladding material is not suppressed to a range below 3.0, so there is a possibility that the actual effective cross-sectional area for the flow of alternating current cannot be guaranteed. As a result, although the cladding material of sample number 21 achieves a lightweight of more than 50% compared with the pure copper material (C1020), there is a possibility that the resistance becomes larger, and it is confirmed that the surface of the aluminum layer is exposed, so it is confirmed that it cannot be provided as a good product.

[0119] In Trial 22 (Comparative Example), a clad material of material number 22 was prepared, a clad material of sample number 22 was formed, and evaluation was performed in the same manner as Trial 1. The clad material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 0.5, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) is selected in such a way that the plate thickness of the copper plate and the aluminum plate becomes 4. In the cladding material, the total thickness is 1.70 mm, the average layer thickness of the copper layer is 0.28 mm, and the average layer thickness of the aluminum layer is 1.13 mm, and the lightweight rate compared with the pure copper material (C1020) is 47%. In the cladding material, the fluctuation value of the copper layer is 2.6, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a range below 3.0, so it is believed that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. Although the surface exposure of the aluminum layer is not confirmed in the cladding material of sample number 22, it does not achieve a lightweight of more than 50% compared with the pure copper material (C1020). Therefore, for example, when it is provided as a conductor suitable for alternating current, there is room for improvement from the perspective of lightweighting or cost reduction.

[0120] In Trial 23 (Example of the present invention), a cladding material of material number 23 was prepared, a cladding material of sample number 23 was formed, and evaluation was performed in the same manner as in Trial 1. The cladding material was prepared so that the ratio of the Vickers hardness of the copper plate to the aluminum plate (B AS / B CS1 , B AS / B CS2 ) is 1.0, and the thickness ratio of the copper layer and the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ) becomes 15. In the cladding material, the total thickness is 1.70 mm, the average thickness of the copper layer is 0.10 mm, and the average thickness of the aluminum layer is 1.50 mm, and the lightweight rate compared with the pure copper material (C1020) is 62%. In the cladding material, the fluctuation value of the copper layer is 1.9, and the surface exposure of the aluminum layer is not confirmed. The fluctuation value of the copper layer of the cladding material is suppressed to a more preferred range of less than 2.0, so it is believed that the actual effective cross-sectional area for the flow of alternating current can be guaranteed. As a result, it was confirmed that the cladding material of sample number 23 can be provided as a cladding material that achieves a lightweight of more than 50% compared with the pure copper material (C1020) while suppressing the resistance to a small level.

[0121] Here, data based on raw material numbers (sample numbers) 1 to 12 and raw material numbers (sample numbers) 15 to 20, where the material of the aluminum plate (aluminum layer) is equivalent to A5052, are shown. Figure 5 . Figure 5 This is a graph showing the relationship between the hardness ratio of the clad material and the fluctuation value of the copper layer of the clad material. Figure 5 The line segment (two-dot chain line) shown corresponds to the ratio of the layer thickness of the copper layer to the aluminum layer of the cladding material (T A / T C1 、T A / T C2 ).exist Figure 5 In the experiment, it was confirmed that the hardness ratio of the cladding material (B AS / B CS1 , B AS / B CS2 ) is larger, the fluctuation value (T C1MAX / T C1MIN and T C2MAX / T C2MIN The larger the fluctuation value, the smaller the tendency. It can be seen from this that the hardness ratio of the cladding material will affect the fluctuation value of the copper layer of the cladding material. Figure 5 In order to improve the weight reduction rate, it is confirmed that the larger the ratio of the thickness of the copper layer and the aluminum layer of the cladding material (TA / T C1 、T A / T C2 ) shows a significant tendency that the greater the fluctuation value of the copper layer of the cladding material, the greater the fluctuation value. It can be seen from this that the ratio of the layer thickness of the cladding material will have a strong influence on the fluctuation value of the copper layer of the cladding material.

[0122] In addition, the data based on sample numbers 1 to 23 are shown. Figure 6 .exist Figure 6 In the figure, (a) is a graph showing the relationship between the ratio of the thickness of the copper layer and the aluminum layer of the cladding material and the fluctuation value of the copper layer of the cladding material. (b) is a graph using the data of A5052 shown in (a) with the vertical axis (the ratio of the thickness of the cladding material) replaced by a logarithmic scale. In addition, the ellipse (dashed circle) shown in (a) corresponds to the material of the aluminum layer of the cladding material (A1050, A5052, A6063). In addition, the line segment (double dotted line) shown in (b) represents an exponential approximation obtained based on the drawing data. In the figure, Figure 6 In A1050 and A5052 shown in (a) and (b), a significant tendency is confirmed that the fluctuation value of the copper layer of the cladding material increases as the ratio of the layer thickness of the cladding material increases in order to improve the lightweight ratio. The significant tendency shows an exponential change, and its approximate formula is, for example, y=1.2065e0.0359x when the ratio of the layer thickness of the cladding material is set to x and the fluctuation value of the copper layer of the cladding material is set to y. It can be seen from this that the ratio of the layer thickness of the copper layer of the cladding material to the aluminum layer has a strong influence on the fluctuation value of the copper layer of the cladding material.

[0123] In addition, if Figure 6 As shown in (a), the distribution of the fluctuation value of the copper layer of the cladding material (refer to the circle shown by the dotted line) changes depending on the hardness of the aluminum layer. For example, the distribution of the fluctuation value of the copper layer combined with A1050 is located on the left side of the curve graph. In addition, the distribution of the fluctuation value of the copper layer combined with A5052, which is harder than A1050, is located on the right side of the curve graph. From the point of view that the distribution of the fluctuation value of the copper layer of the cladding material changes depending on the hardness of the aluminum layer, it is considered that, for example, the distribution of the fluctuation value of the copper layer of the cladding material combined with A3003, which is harder than A1050 but softer than A5052, is located near the middle of the circle of A1050 and the large circle of A5052 in the curve graph.

[0124] In addition, the data based on sample numbers 1 to 23 are shown. Figure 7 .exist Figure 7 In the figure, (a) represents the total thickness of the cladding material (T P (b) is a graph showing the relationship between the thickness of the copper layer of the cladding material (T C1 、T C2(c) is a graph showing the relationship between the thickness of the aluminum layer of the cladding material (T A ) and the fluctuation value of the copper layer of the cladding material. Figure 7 In (a), (b), and (c), no tendency of follow-up change was confirmed in any of the total thickness of the cladding material, the thickness of the copper layer, and the thickness of the aluminum layer relative to the change in the fluctuation value of the copper layer of the cladding material. This shows that the total thickness of the cladding material, the thickness of the copper layer, and the thickness of the aluminum layer do not have a relevant influence on the fluctuation value of the copper layer of the cladding material.

[0125] Next, considering the case where the cladding material of the present invention is provided as a conductor suitable for an alternating current device, such as a portable charger or a wireless power supply, the resistance (AC impedance) of the cladding material is evaluated. Specifically, the cladding materials of sample number 22 (comparative example) and sample number 23 (inventive example) shown in Table 2 are finish-rolled to form cladding materials of sample number 24 (comparative example), 25 (comparative example), 26 (inventive example) and sample number 27 (inventive example) shown in Table 3 with a smaller total thickness. Using the cladding materials of the sample numbers 24 to 27, a measurement sample (width 15 mm, length 150 mm) was prepared. In addition, in order to compare with the cladding material, a plate material shown in Table 4 of a single material was used to prepare a measurement sample (reference example) with the same thickness, width and length as the measurement sample of the cladding material. For the measurement samples of the cladding material and the plate material (inventive example, comparative example), the AC impedance was measured using an LCZ tester (a four-terminal pair method with a distance between the voltage electrodes set to 90 mm) at room temperature (about 25°C).

[0126] Tables 3 and 4 show the AC impedance value (average value) and AC volume resistivity. The AC volume resistivity is a calculated value obtained by dividing the product of the measured AC impedance value (average value) and the cross-sectional area of ​​the test sample (total thickness × width 15 mm or plate thickness × width 15 mm) by the distance between the voltage electrodes during the measurement (90 mm). In addition, the total thickness (T P ), the thickness of the copper layer (T C1 、T C2 ) and the thickness of the aluminum layer (T A ), and the plate thickness of the plate (sample) were measured in the same manner as in the above-mentioned trial production.

[0127] [Table 3]

[0128]

[0129] [Table 4]

[0130]

[0131] <AC impedance value>

[0132] In Table 3, the sample numbers 24 and 25 using A1050 are T A / T C1 and T A / T C2 The ratio of the ... A / T C1 and T A / T C2 The present invention example is about 15 (1:15:1) and the lightweight ratio is 62%. The lightweight ratio of the cladding material and the material of the aluminum layer of sample No. 24 (comparative example) and 26 (the present invention example) are different, but the total thickness is the same, which is 1.360 mm. In addition, the lightweight ratio of the cladding material and the material of the aluminum layer of sample No. 25 (comparative example) and 27 (the present invention example) are different, but the total thickness is the same, which is 0.680 mm.

[0133] As shown in Table 3, the AC impedance values ​​of the cladding materials of sample numbers 24 to 27 are 6.6 mΩ at 10 kHz, which is less than 10 mΩ, and 64 mΩ to 65 mΩ at 100 kHz, which is less than 100 mΩ. This shows that the AC impedance value of the cladding material increases when the frequency of the AC current increases when the total thickness is approximately 0.5 mm to 2.0 mm, more precisely, when the total thickness is 0.5 mm to 1.5 mm. In addition, it is found that the AC impedance value of the cladding material is low in sensitivity to changes in the total thickness of the cladding material, the lightweight ratio, and the material of the aluminum layer, and the substantial change is sufficiently small.

[0134] In addition, in Table 4, sample numbers 28 to 30 are reference examples including plates of a single material. The materials of the plates of the single material of sample numbers 28 and 30 are different, but the plate thickness is the same, which is 1.360 mm. In addition, the materials of the plates of the single material of sample numbers 29 and 31 are different, but the total thickness is the same, which is 0.680 mm. In addition, the plate thickness of the plates of the single material of sample numbers 28 and 29 is different, but the material is the same, which is equivalent to C1020. In addition, the plate thickness of the plates of the single material of sample numbers 30 and 31 is different, but the material is the same, which is equivalent to A1050.

[0135] As shown in Table 4, the AC impedance values ​​of the single-material plates of sample numbers 28 to 31 are all 6.3 mΩ to 6.4 mΩ at 10 kHz and 63 mΩ at 100 kHz. This shows that the AC impedance value of the single-material plate increases as the frequency of the AC current increases. It is also shown that the AC impedance value of the single-material plate is low in sensitivity to changes in plate thickness and material, and the substantial change is sufficiently small.

[0136] As described above, the AC impedance values ​​of the cladding materials shown in Table 3 are 10 mΩ or less at 10 kHz and 100 mΩ or less at 100 kHz, which are roughly equivalent to the single material plate equivalent to C1020 shown in Table 4. Therefore, the cladding material having an AC impedance value roughly equivalent to that of a plate equivalent to C1020 (pure copper material) in practical use from about 10 kHz to about 100 kHz can be said to be sufficiently practical. Based on this, it was confirmed that the resistance of the cladding material of the present invention was suppressed to the same level as that of a plate equivalent to C1020 (pure copper material), and thus it can be used as a conductor.

[0137] <AC volume resistivity>

[0138] In Table 3, the AC volume resistivity of the cladding material of sample Nos. 24 (comparative example) and 26 (inventive example) with different lightweight ratios and aluminum layer materials but the same total thickness of 1.360 mm is 1.5 mΩ·mm and less than 2 mΩ·mm at 10 kHz, and 15 mΩ·mm and less than 20 mΩ·mm at 100 kHz. In addition, the AC volume resistivity of the cladding material of sample Nos. 25 (comparative example) and 27 (inventive example) with different lightweight ratios and aluminum layer materials but the same total thickness of 0.680 mm is 0.7 mΩ·mm and less than 1 mΩ·mm at 10 kHz, and 7 mΩ·mm and less than 10 mΩ·mm at 100 kHz.

[0139] It is thus determined that the AC volume resistivity of the cladding material increases when the total thickness of the cladding material is approximately 0.5 mm to 2.0 mm, more precisely, when the total thickness of the cladding material is 0.5 mm to 1.5 mm, and increases when the frequency of the AC current becomes higher. It is also determined that the AC volume resistivity of the cladding material is low in sensitivity to changes in the lightweight rate of the cladding material and the material of the aluminum layer, and the substantial changes are sufficiently small. In addition, as shown in Table 3, whether C1020 is combined with A1050 with a conductivity of about 60% IACS or with A5052 with a conductivity of about 35% IACS, the AC volume resistivity of the cladding material does not change. Therefore, it can be considered that whether C1020 is combined with, for example, A3003 with a conductivity of about 40% to 50% IACS or with A6063 with a conductivity of about 55% IACS, the AC volume resistivity of the cladding material will not change.

[0140] In Table 4, the AC volume resistivity of the single material plate of sample Nos. 28 (reference example) and 30 (reference example) with different materials but the same plate thickness of 1.360 mm was 1.4 mΩ·mm at 10 kHz and less than 2 mΩ·mm, and 14 mΩ·mm at 100 kHz and less than 20 mΩ·mm. In addition, the AC volume resistivity of the single material plate of sample Nos. 29 (reference example) and 31 (reference example) with different materials but the same plate thickness of 0.680 mm was 0.7 mΩ·mm at 10 kHz and less than 1 mΩ·mm, and 7 mΩ·mm at 100 kHz and less than 10 mΩ·mm.

[0141] Based on this, it is found that the AC volume resistivity of a plate made of a single material increases as the plate thickness increases and increases as the frequency of the AC current increases. In addition, it is found that the AC volume resistivity of a plate made of a single material is low in sensitivity to changes in the material of the plate and the substantial change is sufficiently small.

[0142] Based on the above, it is confirmed that the AC volume resistivity of the cladding material shown in Table 3 and the plate of the single material shown in Table 4 is approximately the same value if the overall thickness (total thickness in the case of the cladding material, plate thickness in the case of the pure copper material) and the frequency are the same. Specifically, the AC volume resistivity of the cladding material and the plate of the single material with an overall thickness of 0.680 mm is less than 1 mΩ·mm at 10 kHz and less than 10 mΩ·mm at 100 kHz. In addition, the AC volume resistivity of the cladding material and the plate of the single material with an overall thickness of 1.360 mm is less than 10 mΩ·mm at 10 kHz and less than 100 mΩ·mm at 100 kHz. Based on this, it was confirmed that when used in practical applications from around 10 kHz to around 100 kHz, the cladding material has an AC volume resistivity that is approximately the same as that of a plate material (pure copper material) equivalent to C1020, so the resistance is suppressed to the same level as that of a plate material (pure copper material) equivalent to C1020, thereby enabling it to be used as a conductor.

[0143] It can be seen from this that the total thickness of the cladding material and the AC volume resistivity can be used to estimate the change tendency of the AC volume resistivity relative to the total thickness of the cladding material. For example, when the total thickness of the cladding material is T P , the change is ΔT P , AC volume resistivity is R V , the change is ΔR V In simple terms, it is caused by R V =ΔR V / ΔT P ×T P Based on the above formula, in the case of 10kHz, according to Table 3, X P When R is 0.680mm V 0.7mΩ·mm, X P R when 1.360mm V is 1.5 mΩ·mm, so ΔR V / ΔT P is about 1.2. Then, using the ΔR V / ΔT P , find the value of X P When R is 0.500mm V is about 0.6 mΩ·mm, find X P R when 2.000mm V is about 2.4 mΩ·mm. Similarly, at 100 kHz, according to Table 3, X P When R is 0.680mm V7mΩ·mm, X P R when 1.360mm V is 15 mΩ·mm, so ΔR V / ΔT P is about 12. Then, using the ΔR V / ΔT P , find the value of X P When R is 0.500mm V is about 6 mΩ·mm, find X P R when 2.000mm V It is about 24mΩ·mm.

[0144] From the viewpoint of considering the above-mentioned change tendency, the total thickness of the cladding material (T P ) is approximately 0.5mm or more and 2.0mm, more precisely, in the case of 0.5mm to 1.5mm, the AC volume resistivity of the cladding material becomes less than 10mΩ·mm at 10kHz and becomes less than 100mΩ·mm at 100kHz. This level of AC volume resistivity is sufficiently small for the use of conductors for AC current. When used in practical applications from around 10kHz to around 100kHz, a cladding material having an AC volume resistivity approximately equivalent to that of a plate material (pure copper material) equivalent to C1020 can be said to be fully practical. In addition, when the cladding material is used as a conductor for AC current in practice, the AC volume resistivity of the cladding material can be used if it is less than 20mΩ·mm (preferably less than 15mΩ·mm, more preferably less than 10mΩ·mm) at 10kHz, and can be used if it is less than 200mΩ·mm (preferably less than 150mΩ·mm, more preferably less than 100mΩ·mm) at 100kHz.

[0145] Explanation of symbols

[0146] 1: Cladding material

[0147] 11: Copper layer (first copper layer)

[0148] 12: Copper layer (second copper layer)

[0149] 13: Aluminum layer

[0150] 14a: Diffusion layer

[0151] 14b: Diffusion layer

[0152] T P : Thickness of cladding material (average total thickness)

[0153] T A : Average thickness of aluminum layer

[0154] T C1 : Average thickness of the copper layer (first copper layer)

[0155] T C1MAX : Maximum thickness of the copper layer (first copper layer)

[0156] T C1MIN : Minimum thickness of the copper layer (first copper layer)

[0157] T C2 : Average thickness of copper layer (second copper layer)

[0158] T C2MAX : Maximum thickness of the copper layer (second copper layer)

[0159] T C2MIN : Minimum thickness of the copper layer (second copper layer)

Claims

1. A cladding material, comprising a first copper layer, an aluminum layer and a second copper layer stacked and crimped in this order, wherein: Assuming the average total thickness of the cladding material is T P The average thickness of the aluminum layer is T A , the average thickness of the first copper layer is T C1 , the average layer thickness T C1 The maximum thickness of the first copper layer within the measurement object range is T C1MAX and the minimum layer thickness is T C1MIN , the average thickness of the second copper layer is T C2 , the average layer thickness T C2 The maximum thickness of the second copper layer within the measurement object range is T C2MAX and the minimum layer thickness is T C2MIN When 0.5mm≦T P ≦2.0mm, meet 6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26, and 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.

0.

2. The cladding material according to claim 1, wherein: The AC impedance value of a sample having a width of 15 mm was measured by a four-terminal pair method with a distance between voltage electrodes set to 90 mm at room temperature, and the AC volume resistivity obtained using the AC impedance value when the frequency of the AC current was set to 10 kHz was 20 mΩ·mm or less.

3. The cladding material according to claim 1, wherein: The AC impedance value of a sample having a width of 15 mm was measured by a four-terminal pair method with a distance between voltage electrodes set to 90 mm at room temperature, and the AC volume resistivity obtained using the AC impedance value when the frequency of the AC current was set to 100 kHz was 200 mΩ·mm or less.

4. The cladding material according to claim 1, wherein: The aluminum layer includes an aluminum alloy of the Japanese Industrial Standards A3000 series containing Mn, an aluminum alloy of the Japanese Industrial Standards A5000 series containing Mg, or an aluminum alloy of the Japanese Industrial Standards A6000 series containing Mg and Si.

5. A method for manufacturing a cladding material, comprising a step of preparing a cladding raw material and a step of rolling the cladding material, In the step of preparing the cladding material, the following first copper plate, aluminum plate and second copper plate are prepared: when the average plate thickness of the first copper plate is T CS1 and Vickers hardness is B CS1 , the average thickness of the aluminum plate is T AS and Vickers hardness is B AS , the average thickness of the second copper plate is T CS2 and Vickers hardness is B CS2 When 6≦T AS / T CS1 ≦26 and 6≦T AS / T CS2 ≦26, and meets B AS / B CS1 ≧1.0 and B AS / B CS2 ≧1.0, In the rolling process of the clad material, the Vickers hardness of the first copper layer corresponding to the first copper plate after rolling is set to B C1 The Vickers hardness of the aluminum layer corresponding to the rolled aluminum plate is B A The Vickers hardness of the second copper layer corresponding to the second copper plate after rolling is B C2 When B is satisfied A / B C1 ≧0.5 and B A / B C2 ≧0.5, rolling the first copper plate, the aluminum plate, and the second copper plate prepared in the preparation process of the cladding raw material in a state of being stacked in this order to form a cladding material in which the first copper layer, the aluminum layer, and the second copper layer are stacked and pressed in this order, The manufacturing method of the cladding material comprises the following cladding material: assuming that the average total thickness of the cladding material is T P The average thickness of the aluminum layer is T A , the average thickness of the first copper layer is T C1 , the average layer thickness T C1 The maximum thickness of the first copper layer within the measurement object range is T C1MAX and the minimum layer thickness is T C1MIN , the average thickness of the second copper layer is T C2 , the average layer thickness T C2 The maximum thickness of the second copper layer within the measurement object range is T C2MAX and the minimum layer thickness is T C2MIN When 0.5mm≦T P ≦2.0mm, meet 6≦T A / T C1 ≦26 and 6≦T A / T C2 ≦26, and 1.0≦T C1MAX / T C1MIN ≦3.0 and 1.0≦T C2MAX / T C2MIN ≦3.

0.

6. The method for manufacturing a cladding material according to claim 5, wherein: In the rolling process of the clad material, the rolling condition is such that 1.0≦T C1MAX / T C1MIN ≦2.5 and 1.0≦T C2MAX / T C2MIN The rolling is performed in a manner of ≦2.5 to form a clad material in which the first copper layer, the aluminum layer, and the second copper layer are stacked and pressed in this order.

7. The method for manufacturing a cladding material according to claim 5, wherein: The aluminum plate includes an aluminum alloy of the Japanese Industrial Standards A3000 series containing Mn, an aluminum alloy of the Japanese Industrial Standards A5000 series containing Mg, or an aluminum alloy of the Japanese Industrial Standards A6000 series containing Mg and Si.

Citation Information

Patent Citations

  • Plate-like conductor for bus bar and bus bar composed of the same

    JP2013143257A